Copyright for archivists and records managers - Padfield, Timothy (Facet, 2010)
Outlines copyright law in the UK with special reference to materials relevant to archive and records collections, notably unpublished works. This book also offers advice on rights in the electronic environment and the problems associated with rights clearance; and covers related areas such as moral rights and rights in databases.